Perlindungan Hukum bagi Konsumen dalam Transaksi Elektronik di Platform Shopee Indonesia - Selen Tresnawati; Syaharani Meylian; Nabila Izni Anandhira (Letterlijk, 2025)
Consumer protection law aims to provide legal safeguards for consumers in Indonesia. The development of information technology has transformed the pattern of buying and selling transactions from conventional methods to digital platforms. In the digital era, online trading has become increasingly prevalent, presenting new challenges in the field of contract law. Legal protection is essential to ensure that consumers’ rights are protected from fraud. Shopee, as one of the largest e-commerce platforms in Indonesia, has become a major venue for online transactions. While offering convenience and efficiency, transactions conducted via Shopee also pose various issues that may harm consumers. This article aims to analyze the forms of legal protection available to Indonesian consumers in transactions conducted through Shopee and to evaluate the effectiveness of their implementation based on prevailing regulations. This research explores the legal protection efforts that can be provided to consumers in purchase transactions on the Shopee platform and how such protections are applied in online transactions.